Hidden fires / Sairish Hussain. - Hussain, Sairish (HQ, 2025)
Ramadan, 2017. Yusuf wakes up in the middle of the night to pray. His routine is always the same, but something tells him that tonight is different. Yellow flames blur Yusuf's vision, and the laughter of a small child echoes in his ears. But this time, the red, smoke-filled skies aren't just in his memory. Miles away, Rubi is also awake. On the television, she watches reports of a devastating fire in London. She is already anxious when her parents send her to stay with her Grandpa Yusuf, whose conservative house rules are almost as unbearable as the loneliness she feels at home. Yusuf's lifestyle does not gel with Rubi's. But when she finds him scared and confused one night, it becomes clear that there's more to her grandfather than Rubi ever considered. As Yusuf grapples with the past, Rubi is determined to save him. But the memories that are recovered are more painful than she could have imagined.